2017
DOI: 10.5935/1980-6906/psicologia.v18n3p115-126
|View full text |Cite
|
Sign up to set email alerts
|

Assistência dos cuidadores nas atividades de autocuidado de crianças em acolhimento institucional

Abstract: Sistema de avaliação: às cegas por pares (double blind review). Universidade Presbiteriana Mackenzie.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The AHEMD-IS is an instrument based on the reports of parents or caregivers 4,9,16 . The version for children between three and 18 months of age consists of thirty-five questions related to the home environment divided into four dimensions: physical space (internal and external spaces of the home); variety of stimulation (the extent to which the parent/caregiver stimulates the child); toys that enable the practice of fine motor skills (toys of manipulation); and toys that enable the practice of gross motor skills (those that make the children move and walk).…”
Section: Procedures and Outcomes Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…The AHEMD-IS is an instrument based on the reports of parents or caregivers 4,9,16 . The version for children between three and 18 months of age consists of thirty-five questions related to the home environment divided into four dimensions: physical space (internal and external spaces of the home); variety of stimulation (the extent to which the parent/caregiver stimulates the child); toys that enable the practice of fine motor skills (toys of manipulation); and toys that enable the practice of gross motor skills (those that make the children move and walk).…”
Section: Procedures and Outcomes Of Interestmentioning
confidence: 99%
“…The version for children between three and 18 months of age consists of thirty-five questions related to the home environment divided into four dimensions: physical space (internal and external spaces of the home); variety of stimulation (the extent to which the parent/caregiver stimulates the child); toys that enable the practice of fine motor skills (toys of manipulation); and toys that enable the practice of gross motor skills (those that make the children move and walk). This instrument was translated and validated to Portuguese language and the results suggested that it is useful for the assessment of the quantity and quality of affordances in the home environment 4 . Final scores are obtained using a calculator designed by the original instrument (Supplement 1 -AHEMD-IS Calculator 3 to 11 months Beta 1.0.xls; Supplement 2 -AHEMD-IS Calculator 12 to 18 months Beta 1.0.xls).…”
Section: Procedures and Outcomes Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Cavalcante, Silva e Magalhães (2010) pontuam que nem sempre as condições familiares que levaram crianças e adolescentes a serem acolhidos institucionalmente são totalmente superadas pela família durante o acolhimento, o que dificulta a reinserção. A ausência da garantia de seus direitos básicos, como direito à saúde, à educação, ao emprego, entre outros evidencia a complexidade da questão, e demonstra a importância de compreender esses aspectos sociais presentes no cotidiano das famílias das crianças e adolescentes acolhidos (Azevedo, Cavalcante, Heumann, & Torres, 2016;Siqueira & Dell'Aglio, 2007). Nesse sentido, o estudo de Rosa, Nascimento, Matos e Santos (2012) verificou que, apesar de a maioria dos acolhidos manter vínculos positivos com pelo menos um familiar e dos esforços da equipe técnica, há a dificuldade nos processos de reinserção.…”
Section: Procedimentos Adotados Para a Reinserçãounclassified